Specific Binding of Cholera Toxin to Isolated Intestinal Microvillous Membranes - Walker, W. Allan (1974)
A sucrose density gradient assay was used to demonstrate the specificity and saturation of the binding of [(125)I]cholera toxin to isolated intestinal microvillous membranes from rat small intestine. When the toxin is first complexed to antitoxin and then exposed to intestinal membranes, the binding of cholera toxin is inhibited. To emphasize the physiologic importance of these observations, similar concentrations of [(125)I]cholera toxin were shown to stimulate the accumulation of cyclic AMP in mucosal homogenates and to increase the secretion of fluid into intestinal loops, whereas the same concentrations of toxin mixed with antitoxin had no effect on cyclic AMP accumulation. These studies suggest that cholera toxin attaches to brush border binding sites before exerting its biologic effect and that local intestinal antibody protection against cholera toxin may be due to inhibition of toxin attachment to these binding sites.